Pearls & Oy-sters: Salt and Pepper Sign, PLNTY for Drug-Resistant Epilepsy. (18th April 2023) - Paredes-Aragón, Elma M.; AlKhaldi, Norah A.; Burneo, Jorge G.; Lee, Donald; Ang, Lee C.; Steven, David; MacDonald, Maria; Herrera-Aramburú, Manuel; Mirsattari, Seyed M.
Abstract : Drug-resistant epilepsy, defined as the failure of 2 or more antiseizure medications to achieve seizure freedom, is responsible for 2/3 of epilepsy cases. Tumors are responsible for up to 15% of all adult onset and up to 6% of childhood onset epilepsies. Among these tumors, commonly known subtypes DNET, ganglioglioma, and low-grade astrocytoma are often suspected. New advances in tumor classification have been made, with genetics playing a key role in tumor classification. Polymorphic low-grade neuroepithelial tumor of the young (PLNTY) is a highly epileptogenic subtype of tumors that may mimic low-grade gliomas but offer pathologic and genetic clues: oligodendroglioma-like cellular components and infiltration patterns and strong CD34-immunopositive stain. In addition, a key finding is radiologic: a unifocal abnormality best seen on MRI brain in FLAIR sequence as the "salt and pepper sign" and calcifications appreciated on CT head.